Ekstraksi dan karakterisasi glukosamin dari cangkang udang vaname (Litopenaeus vannamei) dengan metode hidrolisis bertekanan: Extraction and characterization of glucosamine from vannamei shrimp (litopenaeus vannamei) shell using pressure hydrolysis method - Muhammad Sujatmiko; Mala Nurilmala; Kustiariyah Tarman (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Glucosamines belong to the group of amino sugars and act as a precursor for the biosynthesis of glycosylated proteins and lipids in the body. The chemical, biological, and fermented extraction of glucosamine has not yet yielded optimal results. Pressurized hydrolysis treatment is needed to increase the yield of glucosamine. This study aimed to determine the characteristics of pressurized acid glucosamine extract from vannamei shrimp shell. The characteristics observed included the chemical composition, yield, degree of deacetylation, spectrum of functional groups, heavy metal contamination, and appearance. The chemical and heavy metal composition indicate the quality of shrimp shell are of standard allowed. Chitosan had a moisture content of 4.62%, ash content of 0.31%, protein content of 3.03%, deacetylation degree of 78.44%, viscosity of 222 cPs, flaky appearance, brownish-white color, and odorless. Pressurized acid extraction yielded white brownish glucosamine powder. The highest glucosamine yield was found in the 5% HCl acid extraction treatment at a pressure of 0.45 atm. The best glucosamine was obtained from the combined treatment of acid and pressure with the yield and degree of deacetylation that complied with the quality requirements of glucosamine.